2010
DOI: 10.1103/physrevb.81.174527
|View full text |Cite
|
Sign up to set email alerts
|

Effect of spin-orbit coupling on the electron-phonon interaction of the superconductors Pb and Tl

Abstract: The influence of spin-orbit coupling ͑SOC͒ on the electron-phonon interaction and on the pairing strength is investigated for Pb and Tl within density-functional theory. For Pb we find that SOC increases the coupling constant by 44%, solving the longstanding puzzle of too small values obtained consistently in previous first-principles calculations. The origin of the SOC-induced enhancement of lies both in a softening of the phonon spectrum and in an increase in the electron-phonon coupling matrix elements. In … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
106
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 94 publications
(115 citation statements)
references
References 38 publications
9
106
0
Order By: Relevance
“…This blueshift is well understood now and arises from the overestimation of the phonon frequencies in the absence of spin-orbit coupling in our calculation. 64,65 Our calculated electron-phonon coupling λ=1.24 lies in between the values reported in previous theoretical studies, 39,62,63 although it is somewhat smaller than the value 1.55 obtained from tunneling measurements 59 owing to the neglect of spin-orbit coupling. Figure 2 shows the solutions of the isotropic Eliashberg equations Eqs.…”
Section: B Leadsupporting
confidence: 61%
“…This blueshift is well understood now and arises from the overestimation of the phonon frequencies in the absence of spin-orbit coupling in our calculation. 64,65 Our calculated electron-phonon coupling λ=1.24 lies in between the values reported in previous theoretical studies, 39,62,63 although it is somewhat smaller than the value 1.55 obtained from tunneling measurements 59 owing to the neglect of spin-orbit coupling. Figure 2 shows the solutions of the isotropic Eliashberg equations Eqs.…”
Section: B Leadsupporting
confidence: 61%
“…2,7,8 The lifetime or the linewidth (inverse lifetime) is an essential quantity, describing the decay of electron (hole) excitations 7,9 which are important in many processes such as photochemical and catalytical reactions. 10,11 Lead as a strong-coupling superconductor has been a focus of various theoretical studies of electron-phonon coupling properties, 6,[12][13][14][15][16][17][18][19][20][21] and a very detailed information concerning the e-ph interaction at the Fermi level (E F ) is now available. 13,14,[16][17][18][19]21 Recent ab initio local-density calculations 21 have shown that the strength of electronphonon interaction, λ(E F ), is strongly influenced by spin-orbit coupling (SOC).…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Lead as a strong-coupling superconductor has been a focus of various theoretical studies of electron-phonon coupling properties, 6,[12][13][14][15][16][17][18][19][20][21] and a very detailed information concerning the e-ph interaction at the Fermi level (E F ) is now available. 13,14,[16][17][18][19]21 Recent ab initio local-density calculations 21 have shown that the strength of electronphonon interaction, λ(E F ), is strongly influenced by spin-orbit coupling (SOC). The calculations including SOC revealed that relativistic corrections increase λ(E F ) by 44% from 1.08 up to 1.56, solving the long-standing contradiction between too small values of λ(E F ) obtained in previous first-principles calculations 16,18,19 and the experimental eph coupling parameter, 14 λ(E F ) = 1.55.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…25,26 Díaz-Sánchez et al showed that inclusion of SOC is crucial for an improved agreement between calculation and measurement, 26 but it did not provide such a good description as it was the case, for example, for the phonon dispersion of lead. 10 . Very recently, DFPT has been used to investigate the lattice dynamics of Bi(111).…”
mentioning
confidence: 99%